Theoretical analysis and modelling of degradation for III–V lasers on Si. (6th October 2022) - Liu, Jianzhuo; Tang, Mingchu; Deng, Huiwen; Shutts, Samuel; Wang, Lingfang; Smowton, Peter M; Jin, Chaoyuan; Chen, Siming; Seeds, Alywn; Liu, Huiyun
Abstract: InAs/GaAs quantum-dot (QD) lasers offer a promising method to realise Si-based on-chip light sources. However, the monolithic integration of III–V materials on Si introduces a high density of threading dislocations (TDs), which limits the performance of such a laser device in terms of device lifetime. Here, we proposed a kinetic model including a degradation term and a saturation term to simulate the degradation process caused by the TDs in the early stage of laser operation. By using a rate equation model, the current density in the wetting layer, where the TDs concentrate, is calculated. We compared the rate of degradation of QD lasers with different cavity lengths and of quantum-well lasers, where both are directly grown on Si substrates, by varying the fitting parameters in the calculation of current densities in the kinetic model.